21. EFFECTS OF SUPPLEMENT THE READY-TO-DRINK MILK METACARE OPTI ON NUTRITION, DIGESTIVE AND HEALTH STATUS OF KINDERGARTEN CHILDREN (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effect of supplementation the ready to drink milk Metacare Opti on nutritional, digestive and health status of preschool children aged 36-59 months.Method: A controlled intervention study was completed in Ninh Binh province in September 2024 with 120 subjects. The intervention group (60 subjects) used formula supplementation Metacare Opti (a ready-to-drink) twice daily for 2 months and the control group (60 subjects) used a regular diet. The tool is calibrated and applies techniques standards for identifying the nutritional, digestive and health status and avoiding bias in research. Analyze data by SPSS20.0 software and describe by ratios and averages, use of appropriate statistical tools in biomedical research.Results: Results showed positive effects comparing the intervention group vs. the control group: Improved average weight: Weight was higher 0.58 kg (0.91 ± 0.31 kg vs. 0.33 ± 0.17 kg) with statistical significance (p
Keywords: micronutrients; metacare Opti; height; weight; preschool children